Long-term use of anti-D in chronic idiopathic thrombocytopenic purpura - Yaprak, Işın; Çağlayan, Suat; Kansoy, Savaş; Özdoğru, Ece; Bakiler, A. Rahmi; Aydınlıoğlu, Halil (The Turkish Journal of Pediatrics, 1994)
Chronic idiopathic thrombocytopenic purpura is an autoimmune disease characterized by antibody-mediated destruction of platelets. To maintain the platelets above the symptomatic level, we administered anti-D (100 µg for 5 consecutive days) in 19 children with idiopathic thrombocytopenic purpura (ITP). Four patients did not respond to treatment. Fifteen responded with an increase in the average platelet number to 76,000 / µL on the 7th postinjection day. Within 45 days, however, platelets dropped to 27,000 / µL. Three months after this study, two patients from the study group were re-administered anti-D in daily injections for 5 consecutive days, as was done previously. Monthly administration of anti-D in two patients maintained platelets above 30,000 / µL for periods of five and six months.We concluded that monthly administration of anti-D after five consecutive daily injections can maintain platelet levels above the symptomatic level and may provide a corticosteroid-free safe interval of nearly five months.
Keywords: chronic idiopathic thrombocytopenic purpura; anti-D